Improving Vocabulary Mastery Using Pictures For the Eight Grade Students in the School - Usboko, Marsedis; Lasi, Febronia; D Luruk, Fransiska (Jurnal Basicedu, 2024)
Vocabulary mastery is important for the students. Pictures can also provide experiences and understanding of students to be wider, clearer, and not easily forgotten, and more concrete in the memories and associations of students.The purpose of this study are: 1) To know how pictures improve the students’ vocabulary mastery. 2) To categorize the level of students’ vocabulary mastery by using pictures. The method of this research is pre-experimental design. The finding showsthatmeanscoreofpost-test (74) washigher than themean score of pre-test (65) with standard deviation (71). Based on the result the writer conclude that: 1) Picture media is effective enough to increase the eight grade students of SMP Negeri Neonbat vocabulary mastery. It clearly revealed from the result of pre-test and post-test which shown an increasing from 7.88 into 8.96 Therefore, based on this result the writer recommend picture as a media that can be used by the teachers of English to improve their students’ vocabulary mastery. 2) The level of vocabulary mastery of the eight grade students of SMP Negeri Neonbat is categorized in togood. It is proven by their post-test result which showed an increasing from fair level of category (7.88) into good level of category (8.96). The Conclusion/ the impact of vocabulary using picture is the presence of vocabulary will make it easier to understand or master English. Vocabulary will also be able to understand the meaning of words, also know how to spell and behave in different situations. So to help this writer, applying the method using “pictures” aims to increase students’ vocabulary. By using this learning media it can make it easier for students to improve vocabulary skills and not get bored easily so that students’ vocabulary increase